BLTR1 and CD36 Expressing Microvesicles in Atherosclerotic Patients and Healthy Individuals - Sanden, Mathilde; Botha, Jaco; Nielsen, Michael René Skjelbo; Nielsen, Morten Hjuler; Schmidt, Erik Berg; Handberg, Aase (Frontiers in Cardiovascular Medicine, 2018)
Aims: Monocytes/macrophages play a crucial role in the development, progression, and complication of atherosclerosis. In particular, foam cell formation driven by CD36 mediated internalisation of oxLDL leads to activation of monocytes and subsequent release of microvesicles (MVs) derived from monocytes (MMVs). Further, pro-inflammatory leukotriene B4 (LTB4) derived from arachidonic acid promotes atherosclerosis through the high-affinity receptor BLTR1. Thus, we aimed to investigate the correlation between different MMV phenotypes (CD14+ MVs) on the one hand, and arachidonic acid and eicosapentaenoic acid contents in different compartments including atherosclerotic plaques, plasma, and granulocytes on the other. Methods and Results: Samples from patients with femoral atherosclerosis and healthy controls were analysed on an Apogee A60 Micro-PLUS flow cytometer. Platelet-poor plasma was labelled with lactadherin-FITC, anti-CD14-APC, anti-CD36-PE, and anti-BLTR1-AF700. Eicosapentaenoic acid and arachidonic acid content in different compartments in patients were analysed using gas chromatography. Compared to controls, patients had lower levels of BLTR1+ MVs (p=0.007), CD14+BLTR1+ MVs (p=0.007), and CD14+BLTR1+CD36+ MVs (p=0.001). Further, in patients CD14+ MVs and CD14+CD36+ MVs correlated inversely with arachidonic acid in granulocytes (r=-0.302, p=0.039 and r=-0.322, p=0.028, respectively). Moreover, CD14+CD36+ MVs correlated inversely with arachidonic acid in plasma phospholipids in patients (r = -0.315, p = 0.029), and positively with triglyceride in both patients (r = 0.33, p = 0.019) and controls (r = 0.46, p = 0.022). Conclusion: This is the first study of its kind and thus the results are explorative and only indicative. BLTR1+ MVs and CD14+CD36+ MVs has potential as markers of atherosclerosis pathophysiology, but this needs further investigation.